Anthropometric profile and motor performance of junior badminton players - Angioluci Diniz Campos, F.; Bobroff Daros, L.; Mastrascusa, V.; Dourado, A. C.; Reeberg Stanganelli, L. C. (Brazilian Journal of Biomotricity, 2009)
This study aimed at assessing the anthropometric profile and motor performance of young badminton athletes. The sample included 20 athletes (10 male athletes, mean age 17.24±1.18 years and 10 female athletes, mean age 15.21±2.06 years) playing in the Brazilian junior badminton team. The following variables were assessed: body weight; height; skinfold thicknesses; abdominal strength/resistance; medicine ball throw; 20-meter speed; vertical jumps: vertical squat jump, countermovement vertical jump; and aerobic power. Descriptive statistics (means and standard deviations) and student`s t-test were used for data analysis. Differences were considered significant at the level of p<0.05. The results found in this study regarding male and female athletes were, respectively: body weight (68.0±7.8 and 61.74±6.85 kg), height (172.4±0.5 and 163.8±0.3 cm), sum of seven skinfolds (83.21±22.02 and 131.58±29.36 mm), abdominal strength/resistance (33±3.3 and 28±5.8 n), medicine ball throw (7.54±1.01 and 6.98±0.78 m), 20-meter speed (3.12±0.08 and 3.5±0.14 seconds), vertical squat jump (36.7±6.0 and 27.2±2.1 cm), countermovement vertical jump (39.3±5.7 and 28.1±2.4 cm) and VO2max (49.68±2.48 and 42.92±2.94 ml/kg/min-1). The results of this study describe anthropometric and motor test characteristics of young athletes playing in the Brazilian junior badminton team. They can also help coaches in identifying and choosing new badminton athletes.